Isolation of Carrot Chromoplasts and Assessment of Their Carotenoid Content and Bioaccessibility - Ana M. Benítez-González; Lourdes Gómez-Gómez; Oussama Ahrazem; Patricia Esquivel; Carla M. Stinco; Antonio J. Meléndez-Martínez (Molecules)
The bioaccessibility (fraction of compounds released from the food matrix and available for absorption) and carotenoid content of carrot chromoplasts obtained through high-speed centrifugation using sucrose gradients were assessed. Three chromoplast bands were isolated, corresponding to sucrose gradients between 15 and 30%, 30 and 40%, and 40 and 50%. Total carotenoid levels increased ~2.8-fold when comparing the fractions of the bands of the lowest and highest sucrose gradients. The carotenoid profiles of the bands were similar. Phytoene and phytofluene accounted for approximately 3 and 4%, respectively, while ζ-carotene made up about 3%. Provitamin A carotenoids comprised about 85% of the total carotenoids in the respective fractions. Lutein content varied among fractions, with 1.61% in the 15/30% band and 0.77% in the 40/50% sucrose band. Similar micellar carotenoid profiles were also observed across fractions. α-carotene and β-carotene accounted for 8% and 0.2% of the total carotenoid content, respectively, while ζ-carotene constituted 19%. Lutein content in micelles ranged from 0.5% in the highest sucrose content fractions to 3.2% in the lowest. Phytoene and phytofluene were the predominant carotenoids in micelles. They accounted for 41.7% and 28.4%, respectively, together representing 70% of all carotenoids, with no differences among fractions. Colourless carotenoids were more readily incorporated into micelles, followed by ζ-carotene, lutein, and provitamin A carotenoids.